miR-146a ameliorates liver ischemia/reperfusion injury by suppressing IRAK1 and TRAF6. - Weiwei Jiang; Liangliang Kong; Qingfeng Ni; Yeting Lu; Wenzhou Ding; Guoqing Liu; Liyong Pu; Weibing Tang; Lianbao Kong (PLoS ONE, 2014)
A critical role of the Toll-like receptor(TLR) and its downstream molecules, including IL-1 receptor-associated kinase 1(IRAK1) and tumor necrosis factor receptor- associated factor 6(TRAF6), in the pathogenesis of liver ischemia/reperfusion (I/R) injury has been documented. Recently a microRNA, miR-146a, was identified as a potent negative regulator of the TLR signaling pathway. In this study, we investigated the role of miR-146a to attenuate TLR signaling and liver I/R injury in vivo and in vitro. miR-146a was decreased in mice Kupffer cells following hepatic I/R, whereas IRAK1 and TRAF6 increased. Overexpression of miR-146a directly decreased IRAK1 and TRAF6 expression and attenuated the release of proinflammatory cytokines through the inactivation of NF-κB P65 in hypoxia/reoxygenation (H/R)-induced macrophages, RAW264.7 cells. Knockdown experiments demonstrated that IRAK1 and TRAF6 are two potential targets for reducing the release of proinflammatory cytokines. Moreover, co-culture assays indicated that miR-146a decreases the apoptosis of hepatocytes after H/R. In vivo administration of Ago-miR-146a, a stable version of miR-146a in vivo, protected against liver injury in mice after I/R via inactivation of the TLR signaling pathway. We conclude that miR-146a ameliorates liver ischemia/reperfusion injury in vivo and hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6.